Assessing the effectiveness of lean service principle on control and maintenance of the wage bill at Management Services Division, Eswatini / Sabelo G. Sifundza and Md Humayun Kabir - G. Sifundza, Sabelo; Kabir, Md Humayun (Faculty of Accountancy, 2019)
The Government of Eswatini (GoE) civil service wage bill continues to rise despite the implementation of Lean Service Principle by Management Services Division (MSD) to contain the wage bill to manageable levels. So far, there are no tangible outcomes that indicate that the principles as applied have been effective in the reduction of the wage bill. Thus, this research aims to examine the question why the Lean Service Principle failed to effectively slow the rampant growth of the civil service wage bill in the Kingdom of Eswatini? The study investigated the wage bill push-factors and the shortcomings of the Lean Service Principle and Just-In-Time (JIT) Technique in the management and reduction of the GoE civil service wage bill. The study found that the techniques used were not designed for the specific control of the wage bill. They are designed for value creation in the delivery of goods or services to the end-user. They are customer centric techniques. To this end, the MSD has been applying the wrong methodologies in wage bill control, which has been evident by the continued yearly increase of the wage bill. The study recommends that Lean Service Principle and the JIT technique should not be used to control and/or manage the wage bill, but must be used for process and systems improvement to create customer value. This study will enable Cabinet to make an appropriate decision on the mandate and future of the MSD, as there have been growing calls to disband the division due to the failure to reduce and/or control the wage bills as that is the core mandate of the division.